Mechanistic transcriptome comprehension of Chlamydomonas reinhardtii subjected to black phosphorus - Pavel Chaloupsky; Martina Kolackova; Marketa Dobesova; Ondrej Pencik; Vladimira Tarbajova; Petr Capal; Pavel Svec; Andrea Ridoskova; Zuzana Bytesnikova; Pavlina Pelcova; Vojtech Adam; Dalibor Huska (Ecotoxicology and Environmental Safety, 2024)
Two-dimensional materials have recently gained significant awareness. A representative of such materials, black phosphorous (BP), earned attention based on its comprehensive application potential. The presented study focuses on the mode of cellular response underlying the BP interaction with Chlamydomonas reinhardtii as an algal model organism. We observed noticeable ROS formation and changes in outer cellular topology after 72 h of incubation at 5 mg/L BP. Transcriptome profiling was employed to examine C. reinhardtii response after exposure to 25 mg/L BP for a deeper understanding of the associated processes. The RNA sequencing has revealed a comprehensive response with abundant transcript downregulation. The mode of action was attributed to cell wall disruption, ROS elevation, and chloroplast disturbance. Besides many other dysregulated genes, the cell response involved the downregulation of GH9 and gametolysin within a cell wall, pointing to a shift to discrete manipulation with resources. The response also included altered expression of the PRDA1 gene associated with redox governance in chloroplasts implying ROS disharmony. Altered expression of the Cre-miR906–3p, Cre-miR910, and Cre-miR914 pointed to those as potential markers in stress response studies.